THE EFFECT OF WORK ASSESSMENT ACHIEVEMENT AND CAREER DEVELOPMENT TO WORK PRODUCTIVITY THROUGH WORK SATISFACTION - Wulan, I.G.A Purnama; Zani, Andri Yan Prima (Journal of Research in Business, Economics, and Education, 2019)
Human resources are organizational assets. The Increase of employe productivity can not be separated from their job satisfaction and the condition in the organization. Job satisfaction is strongly influenced by job performance appraisal and career development in organization. This study observes the effect of performance appraisal and career development on work productivity with the mediation of job satisfaction. The study was conducted in Educational Institutions in Depok, with  of 86 employees as the samples. The study found that assessment of work performance and career development has an effect on job satisfaction. Job satisfaction also affects work productivity. This research found that job satisfaction is not a mediation between performance appraisal and career development towards work productivity.